The strange death of Europe : immigration, identity, Islam - Murray, Douglas, 1979- (Bloomsbury Continuum, an imprint of Bloomsbury Publishing Plc, 2017)
This book is not only an analysis of demographic and political realities in Europe, but also an eyewitness account of a continent in self-destruct mode. It includes reporting from across the entire continent, from the places where migrants land to the places they end up, from the people who appear to welcome them in to the places which cannot accept them.